2018
DOI: 10.1152/ajprenal.00084.2018
|View full text |Cite
|
Sign up to set email alerts
|

Differences in renal ammonia metabolism in male and female kidney

Abstract: Renal ammonia metabolism has a major role in the maintenance of acid-base homeostasis. Sex differences are well recognized as an important biological variable in many aspects of renal function, including fluid and electrolyte metabolism. However, sex differences in renal ammonia metabolism have not been previously reported. Therefore, the purpose of the current study was to investigate sex differences in renal ammonia metabolism. We studied 4-mo-old wild-type C57BL/6 mice fed a normal diet. Despite similar lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
64
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(79 citation statements)
references
References 66 publications
14
64
1
Order By: Relevance
“…NH 4 + excretion is predicted to be 19% higher in women ( Fig. 2E), consistent with the higher ammonia excretion reported in female mice, despite similar protein intake as males [26]. Urea is reabsorbed along most nephron segments, except the descending limbs of the loops of Henle, where urea enters due to the presumed higher interstitial urea concentration ( Fig.…”
Section: Sex Differences In Segmental Transport Under Baseline Conditsupporting
confidence: 85%
“…NH 4 + excretion is predicted to be 19% higher in women ( Fig. 2E), consistent with the higher ammonia excretion reported in female mice, despite similar protein intake as males [26]. Urea is reabsorbed along most nephron segments, except the descending limbs of the loops of Henle, where urea enters due to the presumed higher interstitial urea concentration ( Fig.…”
Section: Sex Differences In Segmental Transport Under Baseline Conditsupporting
confidence: 85%
“…The idea evolved, in part, from observations from different transport profiles between sexes. Males are more proximal tubule-centric with more abundant proximal tubule sodium transporters, NHE3 and Napi2a, and aquaporin-1, associated with a greater sodium reabsorptive capacity and a longer tubular length than females (14,36) . Females have a more distal-centric transport compared to males (47,27), featuring more NCC, phospho-NCC and NCC activity (47,6).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, administration of loop diuretics, which increase sodium delivery to DCT, increases NCC abundance and activity, and also increase the length and volume of the DCT (2,8,15). Because female rodents have shorter proximal tubules with less sodium reabsorbing transporters compared to males, enhanced distal sodium delivery may stimulate a similar DCT adaptation (47,14,27). Here, we combine optical clearing methods, antibody labeling and 3D microscopy with volumetric imaging tools to explore potential sexual dimorphism of the DCT in the basal state, and in response to remodeling stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Another notable feature is the existence of sex differences in the metabolism of ammonia. Experiments in mice have shown that an increased level of basal NH 3 excretion in females is associated not only with differences in the proportion of proximal renal tubules compared to the kidneys of males, but also with higher expression of RhBG and RhCG (Harris et al 2018).…”
Section: General Mechanisms Underlying the Functionality Of Ammonia-cmentioning
confidence: 99%